A biomechanical comparison of the modified Bunnell pullout and Teo intraosseous suture techniques for attachment of tendon to bone. (October 2019) - Ballesteros-Betancourt, Jose; Rosales, Roberto S.; García-Tarriño, Raquel; Rios, Jose; Combalia-Aleu, Andrés; Llusá-Pérez, Manuel
We compared the biomechanical properties of the Teo intraosseous suture technique with the modified Bunnell pullout technique in a cadaver model after a tendon to bone repair. Thirty-six fresh-frozen cadaveric fingers were assigned randomly to three groups (Teo, Bunnell and control groups). They were loaded cyclically from 2 to 15 N at 25 mm/min, for 500 cycles. Gap formation at the repair site was assessed every 100 cycles and then specimens were tested to failure. The Teo group had an approximately 30% smaller gap every 100 cycles and needed 30% more energy to obtain a 2 mm gap than the modified Bunnell group. Displacement after 500 cyclic loads was significantly lower in the Teo group than in the Bunnell group. For the failure of the Teo suture, it was necessary to apply 31% more load than the Bunnell technique.